Photocatalytic cementitious material for self-cleaning and anti-microbial application - Hamdany, Abdul Halim (2019)
In recent years, titanium dioxide (TiO2) has become the most popular photocatalyst for environmental purification due to its capability to completely degrade a large variety of organic pollutants. However, an attempt to widen the scope of TiO2 application is hindered due to wide bandgap of TiO2 that limits the photoactivation of TiO2 only under UV irradiation. In addition, previous work on environmental purification usually employed TiO2 in the form of suspension system for water treatment. Although TiO2 suspension system provides high surface area for photocatalytic reaction and can minimize mass transfer limitation, the widespread use of TiO2 is restricted as suspension system has additional separation problems. This study therefore focused on (1) developing visible light activated TiO2-based photocatalyst for enhanced degradation of organic pollutants under visible light irradiation and (2) immobilization of TiO2 composite on cementitious materials as supporting media for self-cleaning and antimicrobial application.